Android application for colorblind people and its usability testing - Nasrmalek, Shahab; Roslina Ibrahim, Dr.; Faculty of Advanced Informatics School (2014)
Thesis (Sarjana Sains (Pengurusan Teknologi Maklumat)) - Universiti Teknologi Malaysia, 2014